Number of linear extensions of symmetric KLYM posets - Shastri, Aditya (Utilitas Mathematica, 1998)
Lower and upper bounds on the number of linear extensions of symmetric KLYM posets are provided which almost agree in the leading term of the asymptotic expansion of their logarithm, and thus determine the complexity of sorting such posets.